Development of Students’ Musical Potency in Music Learning : What Do Primary School Teachers Perceive? - Resa Respati; Yudi Sukmayadi; Rita Milyartini (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to reveal the phenomenon of teachers’ perception in developing students’ musical potency and to reveal teachers’ efforts in developing musical potency through learning implementation in elementary school. The study method used was a descriptive method with a qualitative approach. The data was collected by interviewing 13 teachers of an elementary school in Tasikmalaya City, West Java, conducting observations, and studying documents. Data analysis used interactive analysis, and its validity was checked by triangulation. The result showed that the teachers did not fully understand the students’ musical potency because the majority of teachers still interpreted the musical potency partially. It implicated in strategy, method, medium, teaching material, and learning evaluation, which were implemented. Therefore, training is needed to improve teachers’ competence relating to musical potency development.